Microanalysis of Multi-Element in Juncus effusus L. by LIBS Technique - 刘晓娜 黄建梅 吴志生 张乔 史新元 赵娜 贾帅芸 乔延江 (Plasma science & technology, 2015)
Laser-induced breakdown spectroscopy （LIBS） was used to decipher the unique multi-elemental characteristics of Juncus effusus L. The spectral fingerprints of Juncus effusus L. were established based on elemental microanalysis via LIBS. Microanalysis and multimode sampling methodologies were designed in this study. The relative standard deviation （RSD） approach was performed to optimize the multi-shot measurements. Taking advantage of the capability with no or minimal sample pre-treatment of LIBS, a thermodynamic chart of four elements （Mg, Ca, Ba, and Na） was created from twelve collection regions. The diagram of elemental distribution on a micro-scale was generated to explore the nature of Juncus effusus L. by LIBS. The results demon- strated that LIBS is a promising technique for rapid elemental microanalysis of heterogeneous samples.